AVALIAÇÃO GEOFÍSICA (GPR, ER E VLF) DO SISTEMA AQÜÍFERO DO PLANALTO DO CAUÍPE - CEARÁ, BRASIL: RESULTADOS PRELIMINARES - Castro, David Lopes de; Branco, Raimundo Mariano Gomes Castelo; Cunha, Luciano Soares da (Águas Subterrâneas, 2000)
A geophysical survey, including Ground Penetrating Radar (GPR), Electrical Resistivity (ER) and Very Low Frequency (VLF), was carried out for recognizing internal geometry in the aquifer system of the Cauípe Highland in the northern part of Ceará State, Brazil. This aquifer is formed by a fine sandy sedimentary cover underlined by weathered crystalline basement. Hydrogeological informations from wells indicate intensely weathered gneissic rocks between 5 and 7 m depth and a groundwater table about 5.5 m depth. A vertical electric sounding (VES) and a GPR profile using 80 MHz center frequency antennas detected a 4.6 m thick sandy overburden and the interface between weathered and fresh basement up to 21 m depth. The top of the fresh gneiss is marked by a fractured zone which was identified in the GPR section, VES and VLF profile. Another GPR section was conducted using a 400 MHz center frequency antennas to improve more details about the uppermost portion of this aquifer. An irregular groundwater table could be observed about 1.2 m depth as well as three sedimentary layers with distinct electric properties. Several areas in the Cauípe Highland are already investigated with the same geophysical procedure to recognize the overall behavior of their aquifer system.